2020
DOI: 10.1111/pace.14120
|View full text |Cite
|
Sign up to set email alerts
|

The association between body temperature and electrocardiographic parameters in normothermic healthy volunteers

Abstract: Background Previous studies reported that hypo‐ and hyperthermia are associated with several atrial and ventricular electrocardiographical parameters, including corrected QT (QTc) interval. Enhanced characterization of variations in QTc interval and normothermic body temperature aids in better understanding the underlying mechanism behind drug induced QTc interval effects. The analysis’ objective was to investigate associations between body temperature and electrocardiographical parameters in normothermic heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The P wave and QRS wave reflect atrial and ventricular depolarization, respectively. [27,28] Of note, multiple studies have revealed a relationship between the P wave and atrial fibrillation. [10,29,30] The QT interval, QTc interval and T wave duration represent ventricular repolarization, and are thus more closely related to the occurrence of ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…The P wave and QRS wave reflect atrial and ventricular depolarization, respectively. [27,28] Of note, multiple studies have revealed a relationship between the P wave and atrial fibrillation. [10,29,30] The QT interval, QTc interval and T wave duration represent ventricular repolarization, and are thus more closely related to the occurrence of ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%